Comparative analyses of saponin, phenolic, and flavonoid contents in various parts of Rhizophora mucronata and Rhizophora apiculata and their growth inhibition of aquatic pathogenic bacteria - Luksamee Vittaya, Uton Charoendat, Sittichoke Janyong, Juntra Ui-eng, Nararak Leesakul (Journal of Applied Pharmaceutical Science, 2022)
Mangrove plants are the source of various secondary bioactive metabolites and have been used in traditional medicine for many diseases. This study aimed to investigate bioactive phytochemical components of two mangrove plants, Rhizophora mucronate and Rhizophora apiculata in the Rhizophoraceae family. Eight extracts of four parts (pod, leaf, twig, and bark) of each plant were prepared by maceration with a methanolic solvent. Phytochemical analysis was conducted through the aid of a standard test and was confirmed by quantitative analysis based on the determination of the total saponin, phenolic, and flavonoid contents. Free radical scavenging activity was studied in vitro by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) methods. Antibacterial activity was performed by the hole-plate diffusion method and determination of minimum inhibitory concentration (MIC) and minimum bactericidal concentration. The pod of R. mucronata predominantly showed the highest total saponin content [8.05 ± 0.50 mg escin equivalent (EE)/g CE], and the bark presented a great amount of phenolic and total flavonoid contents (2.12 ± 0.11 mg gallic acid equivalent/g CE and 6.73 ± 0.25 mg RU/g CE). R. mucronata showed greater free radical scavenging activity than Rhizophora apiculata at a concentration of 100 _g/ml supported by the DPPH and ABTS assays. Antibacterial screening showed that the maximum zone of inhibition was noted for R. mucronata extracts against Streptococcus agalactiae, Aeromonas hydrophila, Vibrio harveyi, and Vibrio parahemolyticus (8.50–13.56 nm). The R. mucronata pod extract had the lowest MIC to only A. hydrophila. Meanwhile, the R. mucronata bark extract had the lowest MIC to S. agalactiae and A. hydrophila. The higher antibacterial activity of R. mucronata extracts was consistent with the greater saponin, phenolic, and flavonoid contents and antioxidant activity of the extracts of these species with a significant value of p < 0.05. The present study highlighted that R. mucronata could be used as a potential source of bioactive compounds against aquatic pathogenic bacteria.
Keywords: Antioxidant, aquatic pathogens, mangrove plant, phytochemical, secondary metabolite